Intraspecific Variation in Drought Response of Three Populations of Cryptocarya alba and Persea lingue, Two Native Species From Mediterranean Central Chile - Alvarez-Maldini, Carolina; Acevedo, Manuel; Dumroese, R. Kasten; González, Marta; Cartes, Eduardo (Frontiers in Plant Science, 2020)
An increase in the severity of drought events on Mediterranean climates highlights the need of using plant material adapted to drought during restoration efforts. Thus, we investigated between-population morpho-physiological differences in Cryptocarya alba and Persea lingue, two native species from Mediterranean central Chile, for traits that could effectively discriminate population performance in response to water restriction (WR) testing. Three populations from each species were subjected to WR treatment and physiological, morphological, and growth parameters were assessed at the beginning and at the end of the experiment. In C. alba, the most xeric population displayed smaller plants with mesophyllous leaves and lower photosynthetic rates indicating a resource saving strategy. Moreover, the xeric population performed better during WR than the most mesic populations, exhibiting higher water use efficiency (iWUE) and maintenance of growth rates. All C. alba populations responded equally to WR in terms of morphology and biomass partitioning. In contrast, differences among P. lingue populations were subtle at the morpho-physiological level with no apparent relation to provenance environmental conditions, and no morphological traits were affected by WR. However, in response to WR application, the most mesic population was, as observed through reduction in relative growth rates, more affected than xeric populations. We attribute such discrete differences between P. lingue provenances to the lower distributional range of selected populations. Our results show that relative growth rates in both species, and iWUE only in C. alba, exhibited population specific responses upon WR imposition; these results correspond with the environmental conditions found at the origin of each populations. Both traits could further assist in the selection of populations for restoration according to their response to water stress.